SKETCH OF A MAP IN THE STUDY OF HISTORICAL GEOGRAPHY AS A SUMMARY OF PAST ENVIRONMENTAL CONDITIONS - Yogi Iswarini Rahayu; Dian Utami; Vincentius Binar Dwi Septian; Muhammad Ageng Nugroho; Shintabella Nurani Waskito (Journal Learning Geography, 2021)
The purpose of creating this article was to illustrate the role of map sketches  in the  learning of  historical geography so important. Displays similarities or differences in past regions and spatial changes  over certain periods. Thus the existence of the map becomes very important in the study, at least as a summary of the environmental conditions of the past m.a. Metode   study literature is the method used in the study of this article.  Data collection is obtained through various literature or books,  journals, articles, the internet, andother sources that are related to the problem discussed. From the  map sketches in the discussion of this article, both map sketches   depicting the Semarang city   area  , sketches of the Mataram kingdom area and sketches of the old  city of  Medan wecan see in the course of time humans never stop utilizing    environment directly or indirectly by changing the environment as needed.